INCREASING EFFICIENCY IN CONSTRUCTION COMPANIES, INTRODUCING DIGITAL METHODS OF INVESTMENT PROJECT MANAGEMENT (British Journal of Global Ecology and Sustainable Development, 2024)
In the dynamic landscape of the construction industry, effective management of investment projects is critical to success. Traditional methods often struggle to keep up with the changing demands of modern construction projects. This article explores the benefits and challenges of incorporating digital methods into investment project management in construction companies. By leveraging technological advances, firms can streamline processes, increase accuracy, enhance collaboration, and ultimately increase efficiency and profitability.